The summer getaway [large type] - Mallery, Susan (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"With her divorce settlement about to run out and a mortgage she can't afford, Robyn Caldwell needs a plan. But how's she supposed to think when her daughter has become the most demanding bride ever, her son won't even consider college, her best friend is on the brink of marital disaster and her ex is making a bad decision that could bring everything crashing down on Robyn's head? When her great-aunt Lillian invites her to Santa Barbara for the summer, Robyn hops on the first plane. The more time Robyn spends with Lillian, the more she sees the appeal in taking chances on dreams, on love, on family. All she has to do is muster the courage to take a chance on herself"--